2014
DOI: 10.2147/ppa.s53504
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-based asthma self-management aid for adolescents (mASMAA): a feasibility study

Abstract: PurposeAdolescents report high asthma-related morbidity that can be prevented by adequate self-management of the disease. Therefore, there is a need for a developmentally appropriate strategy to promote effective asthma self-management. Mobile phone-based technology is portable, commonly accessible, and well received by adolescents. The purpose of this study was to develop and evaluate the feasibility and acceptability of a comprehensive mobile phone-based asthma self-management aid for adolescents (mASMAA) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(173 citation statements)
references
References 43 publications
3
169
0
1
Order By: Relevance
“…[22][23][24][25][26][27][28][30][31][33][34][36][37][38][39][40][41] Developed by Walter Dick and Lou M. Carey [42][43] in 1978, this model considers the stages of analysis, design/development, implementation and evaluation.…”
Section: Methods Used For Developing Mobile Apps In Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][30][31][33][34][36][37][38][39][40][41] Developed by Walter Dick and Lou M. Carey [42][43] in 1978, this model considers the stages of analysis, design/development, implementation and evaluation.…”
Section: Methods Used For Developing Mobile Apps In Healthmentioning
confidence: 99%
“…In relation to the area of specialty of the mobile apps developed and/or evaluated, the following distribution was evidenced: oncology (hospitalbased, home-based and auditing), [21][22] 19% (4); respiratory diseases (asthma/adolescent and home care), [25][26][27] 14.3% (3); Primary Health Care (health promotion, chronic diseases and cardiovascular diseases), [28][29][30] 14.3% (3); geriatrics, 31-32 9.5% (2); pediatrics (palliative care and care for the newborn) 33,34 9.5% (2); critical-care (adult and neonatal), [35][36] 9.5% (2); kidney disease (hemodialysis), 37 4.8% (1); metabolic disease (obesity), 38 4.8% (1); mental health (depression) 39 4.8% (1); post-operative recovery 40 4.8% (1) and; nutrition (parenteral) 41 4.8% (1).…”
Section: Description Of the Characteristics Of The Studiesmentioning
confidence: 99%
“…Smartphone integration for asthma management has been investigated [66][67][68][69][70] with mixed results. One six-month trial of 288 adolescents and adults with poorly controlled asthma found that smartphone based monitoring had no significant effect on asthma control and self-efficacy in comparison to paper based monitoring [69].…”
Section: Novel Methods Of Communicating Adherence Datamentioning
confidence: 99%
“…This is different to an EMD automatically syncing recorded data with a mobile phone, such as in the SmartTouch AV and Propeller devices. A similar study investigated the feasibility of a text-based system as a method of generating daily reports on a patient's asthma [70]. Results showed a high response rate to text messages of 81%-97% and demonstrated that participants felt using the system helped improve their awareness of symptoms as well as promoting a greater sense of control and better adherence to their asthma [70].…”
Section: Novel Methods Of Communicating Adherence Datamentioning
confidence: 99%
“…J Thorac Dis 2017;9(11):4607-4650 jtd.amegroups.com and internet-based apps may help to complete the network interactivity; particularly as some studies have shown that asthma self-management through electronic devices or internet-based apps can provide higher adherence, better monitoring in asthma symptoms, medical usage and asthma exacerbations (224,225). Thus, similar management methods could be used for AR patients, and patients with both diseases may benefit from the selfmanagement by promoting disease control, awareness of symptoms, treatment adherence, and parent-physician partnerships.…”
Section: Ar With Asthmamentioning
confidence: 99%